Level of knowledge about oral cancer in Dentistry students from 3rd to 5th year - Carla María García San Juan; Blas Jorge González Manso; José Daniel Gil Milá (Medisur)
Foundation: the increasing trend to increase oral cancer, makes it necessary that basic knowledge of general dentistry professional include those which enable their timely diagnosis and treatment. Objective: to describe the level of knowledge about oral cancer of the 3rd, 4th and 5th year dentistry students of the Faculty of Medical Sciences Dr. Raúl Dorticós Torrado, Cienfuegos. Methods: cross-sectional descriptive correlation study conducted from October 2017 to April 2018. The sample consisted of 93 students selected randomly among the three chosen academic years. Level of knowledge was measured in three dimensions: oral cancer epidemiology, clinical treatment and prevention; through a survey designed by the authors, validated by a group of experts. The analysis was done in the SPSS program. Fisher statistical test was used to determine the relationship between the variables with a level of significance of p <0.05. Results: the highest percentage of students has a low level of knowledge regarding oral cancer. The dimension of knowledge with the best results was related to clinical characteristics and treatment; the lowest scores were related to prevention. A statistically significant relationship was found between the level of knowledge, the assistantship and the academic year in which students are at the moment. Conclusions: the students’ knowledge about oral cancer is deficient, so it is important to carry out future interventions for a better approach to the topic.